2018
DOI: 10.5603/gp.a2018.0035
|View full text |Cite
|
Sign up to set email alerts
|

First trimester combined screening for fetal aneuploidies enhanced with additional ultrasound markers: an 8-year prospective study

Abstract: Objectives: To describe our screening population and audit of the performance of first-trimester screening for Down syndrome, based on a combined test, enhanced with additional ultrasound markers, over the whole period of the study. Material and methods:We performed a prospective study from 2009 to 2016, which included 1358 singleton fetuses with a crown-rump length of 45-84 mm. The risk of aneuploidy was calculated using nuchal translucency, fetal heart rate (FHR), and additional markers, such as nasal bone (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
1
3
0
3
Order By: Relevance
“…If this test was enhanced by combining it with the other USG parameters (nasal bone, ductus venosus, and tricuspid regurgitation), the detection rate was observed to improve and reached 91%-96%. 15 In the present study, the highest fetal chromosomal anomaly rate was obtained in pregnant women who underwent the CVS (33.33%) procedure; this finding was also consistent with the literature. 4 It is, therefore, proposed that the first-trimester screening tests are efficient in diagnosing fetal aneuploidy and that the major structural anomalies that could be diagnosed in the first trimester are more related to the chromosomal anomalies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…If this test was enhanced by combining it with the other USG parameters (nasal bone, ductus venosus, and tricuspid regurgitation), the detection rate was observed to improve and reached 91%-96%. 15 In the present study, the highest fetal chromosomal anomaly rate was obtained in pregnant women who underwent the CVS (33.33%) procedure; this finding was also consistent with the literature. 4 It is, therefore, proposed that the first-trimester screening tests are efficient in diagnosing fetal aneuploidy and that the major structural anomalies that could be diagnosed in the first trimester are more related to the chromosomal anomalies.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it would be more convenient to use detailed USG along with the combined test to detect fetal aneuploidy in the first trimester, as stated in the literature as well. 15 It has been reported previously in the literature that the most common indications for amniocentesis were high risk in triple screening test, AMA, and positive USG findings, and that the most common fetal chromosomal anomaly observed was trisomy 21. 12,13 The present study revealed screening test positivity and major structural anomaly in the USG as the most common invasive procedure indications, while the most common fetal chromosomal anomaly revealed in the present study was trisomy 21.…”
Section: Discussionmentioning
confidence: 92%
“…A few reports of DS screening performance have indicated good national results, although from a single medical unit. For example, one single-center audit in Romania has examined performance using different software programs, and reported similar results compared with international specialized centers [24]. Additionally, an analysis of the systematic application of FMF software in Filantropia Hospital between 2010-2019 revealed a prenatal aneuploidy detection rate of 87.5%, with a 3% false-positive rate, when using nuchal translucency and first-trimester biochemical markers.…”
Section: Discussionmentioning
confidence: 88%
“…A second fetal assessment, was performed routinely between 19-24 weeks of gestation, measuring the CM width and transverse cerebellar diameter (TCD) as previously described (5)(6)(7).…”
Section: Methodsmentioning
confidence: 99%